Development of Intelligent Therapeutic Devices: Integration of New Technologies for theCare of Elderly Adults in Cuenca: ARTRI Phase 2 - Hurtado Crespo , Galo; Novillo , Gina Pamela; Umaquinga-Criollo, Ana C.; Pérez , Juan Marcelo (Data and Metadata, 2025)
Population aging and the increasing prevalence of osteoarthritis pose a significant challenge for geriatric care. According to the VIII Population and Housing Census of Ecuador (2023), older adults constitute 9% of the national population, highlighting the need to implement innovative technologies for rehabilitation. Cuenca, Ecuador, is internationally recognized as one of the preferred cities for foreign older adults as a place of residence. Additionally, according to the National Institute of Statistics and Censuses (INEC), it has a high life expectancy of 79 years, making it an ideal environment for implementing technological solutions in geriatric rehabilitation. This study presents the evolution of ARTRI, an intelligent therapeutic device designed for motor stimulation in older adults with osteoarthritis. The new version incorporates an optimized electronic board with ESP32, improving processing capacity, connectivity, and energy efficiency. Additionally, a digital lock was implemented for code protection, and an acrylic structure was designed to enhance durability and ergonomics. The software has been upgraded with structured databases, cloud storage, and real-time monitoring, enabling efficient therapy supervision. The SCRUM methodology ensured an iterative and agile development process, while a demographic heat map facilitated the strategic distribution of the device in key institutions such as the University of Older Adults in Cuenca. The results demonstrate significant improvements in effectiveness, security, and user acceptance, establishing ARTRI as a scalable and innovative solution in digital health and geriatric rehabilitation.